Tribalism Manifestations in Tribal Conflicts in Southern West Bank - Hammad, Mahmud Muhammad; Al-zeer, Daoud Hasan (Journal of Humanities & Social Sciences, 2021)
The study aimed at answering the main question: What are the manifestations of tribalism that appear in tribal conflicts in southern West Bank? This question is divided into three sub-questions that embodies the reasons for the emergence of tribalism: what are the most important forms of tribalism? And to what extent can these forms be overcome? The researchers used the qualitative method. To collect the data of the study, 20 semi-structured interviews were conducted in-depth with well- experienced tribesmen from Bethlehem and Hebron Governorates. Results of the study showed that there are many reasons that stand behind tribalism and loyalty to the tribe. These reasons were represented in the nature of the epistemological, social, moral, economic, and political structure. This has been contributed to the reproduction of the concept of tribalism leading to the formation of symbolic human capital. The forms of tribalism practices were embodied by killing, revenge, clan domination, tribe recruitment (Fazaah), extreme anger (Forat Addam), and the deportation of the murderer's family and his first-degree relatives (Jalwa). These practices can be attributed to a state of cultural heritage that shows tribesmen how to deal with problems in a way that reserve their mental images as the center of power by location and loyalty. These mental images were associated with false tribal understanding of the whole issue. The results of the study also showed that the Palestinian society in its cognitive, social, ideological and economic structure is identical with the pastoral and agricultural community structure below the advanced industrial level; and that the desired change will not be in the short term. Therefore, there is an urgent need for deep thinking to create a society that is more developed and urbanized within a future vision in favor of the supreme symbol of affair and prestige, which is the homeland and the citizen as a substitute for loyalty of the tribalism concept.
Keywords: manifestations of nervousness; tribalism; clan conflicts